How population and macroeconomic factors is affecting the unemployment rate in Indonesia / Nurul Athirah Mohd Fadil - Mohd Fadil, Nurul Athirah (2022)
The aim of this research is to identify how population and macroeconomic factors that are affecting the unemployment rate in Indonesia. This research represents the unemployment rate (UER) as dependent variable and gross domestic product (GDP), inflation (INF), foreign direct investment (FDI) and population (POP) as independent variables. This study uses the secondary data from World Development Indicators website from the period of 2001 to 2020. Therefore, to collect the data, I use time series and run it by E-views version 12. Hence, there are some methodologies used to identify the significance and relationship such as descriptive analysis, correlation analysis, multicollinearity test, heteroskedasticity test and regression analysis. The overall result of this research shows that there is significance in population (POP) while insignificance result from gross domestic product (GDP), inflation (INF), and foreign direct investment (FDI) towards the unemployment rate (UER).